2000
DOI: 10.1038/71750
|View full text |Cite
|
Sign up to set email alerts
|

DNA methyltransferase Dnmt1 associates with histone deacetylase activity

Abstract: The DNA methyltransferase Dnmt1 is responsible for cytosine methylation in mammals and has a role in gene silencing. DNA methylation represses genes partly by recruitment of the methyl-CpG-binding protein MeCP2, which in turn recruits a histone deacetylase activity. Here we show that Dnmt1 is itself associated with histone deacetylase activity in vivo. Consistent with this association, we find that one of the known histone deacetylases, HDAC1, has the ability to bind Dnmt1 and can purify methyltransferase acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
594
0
4

Year Published

2000
2000
2011
2011

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 877 publications
(612 citation statements)
references
References 29 publications
14
594
0
4
Order By: Relevance
“…These results imply that the action of 5Aza-dC is separate from the induction of promoter demethylation. It is possible that 5Aza-dC disrupts complexes between DNA methyltransferases and histone-modifying proteins [18,19]. Kondo et al [20] have reported that 5Aza-dC dramatically decreases histone H3 Lys-9 methylation, slightly increases Lys-9 acetylation, and moderately increases histone H3 Lys-4 methylation and reactivated gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…These results imply that the action of 5Aza-dC is separate from the induction of promoter demethylation. It is possible that 5Aza-dC disrupts complexes between DNA methyltransferases and histone-modifying proteins [18,19]. Kondo et al [20] have reported that 5Aza-dC dramatically decreases histone H3 Lys-9 methylation, slightly increases Lys-9 acetylation, and moderately increases histone H3 Lys-4 methylation and reactivated gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…In humans and mice mutations in the SWI-SNF proteins, which are involved in chromatin remodeling, result in defects in DNA methylation. A growing list of histone modifying enzymes interact with DNMT1, such as HDAC1 and HDAC2, the histone methyltransferases SUV3-9 and EZH2, a member of the multiprotein Polycomb complex PRC2, which methylates H3 histone at the K27 residue [Fuks et al, 2000[Fuks et al, , 2003bRountree et al, 2000;Vire et al, 2006]. DNMT3a was recently also shown to interact with EZH2 which targets the DNA methylation-histone modification multiprotein complexes to specific sequences in DNA [Vire et al, 2006].…”
Section: The Relationship Between Chromatin and Dna Methylationmentioning
confidence: 99%
“…24,30 Genomic DNA methylation and histone deacetylation are essential but not secluded epigeneticregulating mechanisms. 31 Methylcytosine-binding proteins, which bind to methylated DNA sequences, can recruit HDAC and histone methyltransferases, 32 whereas DNA methyltransferases can directly bind HDAC, representing an interaction between DNA methylation and histone deacetylation. 32,33 Interestingly, TSA alone could result in a more dramatic induction of ASPP1 mRNA expression than 5-aza-dc.…”
Section: Aberrant Expression and Hypermethylation Of Aspp1 In Gestatimentioning
confidence: 99%
“…31 Methylcytosine-binding proteins, which bind to methylated DNA sequences, can recruit HDAC and histone methyltransferases, 32 whereas DNA methyltransferases can directly bind HDAC, representing an interaction between DNA methylation and histone deacetylation. 32,33 Interestingly, TSA alone could result in a more dramatic induction of ASPP1 mRNA expression than 5-aza-dc. Recent studies have discovered that TSA can induce DNA demethylation in some methylated tumorsuppressor genes because of its effect on histone acetylation.…”
Section: Aberrant Expression and Hypermethylation Of Aspp1 In Gestatimentioning
confidence: 99%